Greater Amino Acid Intake Is Required to Maximize Whole-Body Protein Synthesis Immediately after Endurance Exercise Than at Rest in Endurance-Trained Rats, as Determined by an Indicator Amino Acid Oxidation Method. Issue 8 (29th June 2016) - Kato, Hiroyuki; Nakano, Sayako; Inoue, Yoshiko; Takeda, Tomoko; Miura, Kyoko; Nakamura, Taro; Suzuki, Katsuya; Bannai, Makoto
Abstract: Background: The indicator amino acid oxidation (IAAO) method has contributed to establishing protein and amino acid (AA) requirements by determining the optimal protein and AA intake that maximizes whole-body protein synthesis. However, it has not been used with endurance-trained subjects. Objective: This study aimed to determine the optimal AA intake immediately after endurance exercise and at rest in endurance-trained rats by using the IAAO method. Methods: Four-week-old male Fischer rats were divided into a sedentary (SED) group and a trained (TR) group, which underwent treadmill training 5 d/wk for 6 wk at 26 m/min for 60 min/d. On the metabolic trial day, half of the TR group was provided with test diets after daily treadmill running (TR-PostEx). The other half of the TR group (TR-Rest) and all of the SED group were provided with test diets while at rest. The test diets contained different amounts of AAs (3.3–37.3 g ⋅ kg −1 ⋅ d −1 ). Phenylalanine in the test diet was replaced with L-[1- 13 C]phenylalanine. The phenylalanine oxidation rate (PheOx) was determined with 13 CO2 enrichment in breath, CO2 excretion rate, and enrichment of phenylalanine in blood during the feeding period. The optimal AA intake was determined with biphasic mixed linear regression crossover analysis for PheOx, which identified a breakpoint at the minimal PheOx in response to graded amounts of AA intake. Results: The optimal AA intake in the TR-PostEx group (26.8 g ⋅ kg −1 ⋅ d −1 ; 95% CI: 21.5, 32.1 g ⋅ kg −1 ⋅ d −1 ) was significantly higher than in the SED (15.1 g ⋅ kg −1 ⋅ d −1 ; 95% CI: 11.1, 19.1 g ⋅ kg −1 ⋅ d −1 ) and TR-Rest (13.3 g ⋅ kg −1 ⋅ d −1 ; 95% CI: 10.9, 15.7 g ⋅ kg −1 ⋅ d −1 ) groups, which did not differ. Conclusions: Greater AA intake is required to maximize whole-body protein synthesis immediately after endurance exercise than at rest, but not at rest in endurance-trained rats.